Supervivencia y crecimiento de plántulas de encina en función de la intensidad de luz y la disponibilidad de agua (II Congreso Forestal Español, 1997)
The response of holm oak seedlings under a gradient of light and water av ail abilit y is analyzed. Seedling survival under all water levels decreased with increasing light. Conceming seedling morphology, both light and water availability changed biomass allocation to roots, stems and leaves, being light the most important source of variation

SUPERVIVENCIA DE PLANTULAS DE PINO CARRASCA (PINUS HALEPENSIS) y ENCINA (QUERCUS ILEX) EN BOSQUE MIXTOS DE AMBAS ESPECIES (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, survival of holm oak and Aleppo pine seedlings in holm oak stands, Aleppo pine stands and mixed stands, both in cut and uncut plots, is analized. Survival of holm oak seedlings in uncut plots is greater than that of Aleppo pine seedlings in the three types of forest considered. Mortality of seedlings of both species in 9ut plots is considerably smaller than that of uncut plots. K.W.:

Biomass Equations for Quercus ilex L. in the Montseny Massif, Northeastern Spain (Forestry, 1988)
Biomass estimation equations for individual holm oak (Quercus ilex spp. ilex) were developed using data from 71 sample trees. Diameter alone was a strong predictor of biomass, but better biomass estimates were obtained when height and crown projection radius were added to the model. In addition to total above-ground dry weight, different biomass components were calculated: stem (greater than 5 cm in diameter), branches 1 to 5 cm in diameter, branches less than 1 cm in diameter, and foliage. Grouping the trees according to height (taller or shorter than 7 m) and aspect (north-and south-facing slopes) resulted in significantly different allometric equations for most of the components considered. Improved estimates were achieved in many cases when D50 (diameter at 0.5 m) was used instead of DBH. Comparison of the results with other published equations developed for Q.ilex and other oaks showed differences, probably due to morphological diversity of trees and different DBH class distribution of samples used.
10.1093/forestry/61.2.137